GH, IGF-1, and Age Are Important Contributors to Thyroid Abnormalities in Patients with Acromegaly - Xia Wu; Lu Gao; Xiaopeng Guo; Qiang Wang; Zihao Wang; Wei Lian; Wei Liu; Jian Sun; Bing Xing (International Journal of Endocrinology)
Purpose. To determine the prevalence, risk factors, and possible mechanisms of structural and endocrinological changes to the thyroid in acromegaly. Methods. We studied 93 acromegalic patients from PUMCH between January 2013 and December 2013. The demographic and clinical information were recorded. Specimens of pituitary adenomas and thyroid cancer were collected for BRAF mutation assessments. Results. Thyroid morphological abnormalities were found in 72 (77.4%) patients. Three (3.2%) were diagnosed with thyroid cancer. The thyroid gland volume was significantly increased in patients with higher random GH (p=0.01), higher nadir GH (p=0.008), and higher IGF-1 level (p=0.018). Age (p=0.002) was an independent risk factor for thyroid morphological abnormalities in acromegaly. The GH burden was significantly higher in patients with thyroid morphological abnormalities (p=0.036). The BRAF V600E mutation was detected in the PTCs of the two patients with thyroid cancer. Conclusions. Both benign and malignant thyroid abnormalities are increased in the acromegalic population compared to those in the general population. Age at diagnosis is an independent risk factor for thyroid abnormalities, and GH burden may be a partial contributor. Early diagnosis, early treatment, and monitoring of postoperational endocrine levels are important for acromegalic patients.